Modal Manusia dan Transisi Pemuda Fresh Graduates ke Sektor Digital di Masa Pandemi COVID-19 - Feisal Sinaga (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2023)
Youth and digitalization have an essential role in the nation's development Youth as an agent of change, which brings new ideas and innovation. In contrast, digitalization brings changes in terms of efficiency and effectiveness which are able to become a source of new economic growth. The existence of COVID-19 pandemic has caused barriers for youth to enter the workforce since graduate school (school-to-work transition), which is a blessing in disguise as technology adoption accelerates and creates new job opportunities for youth as it requires digital skills. Youth which are considered as adaptive to technology by nature, are considered to have the opportunity to increase their work participation through transitioning jobs to the digital sector. This study aims to analyze the influence of human capital in the form of education and training in fresh graduates' youth on opportunities to transition jobs to the digital sector. The data source and method used resulted from the August 2021 National Labor Force Survey (Sakernas) and multinomial logistic regression. The study result shows that education and training influence youth's transition to the digital sector. Young fresh graduates with higher education have a 1.491. times higher tendency to make the transition to the digital sector. Participation in training for youth will also increase the tendency of 1,525 times for youth with secondary education and 1,239 times for youth with higher education to transition to the digital sector. Pre-Employment Program (Prakerja) participation will also increase the tendency by 1,314 times to transition to the digital sector. Other findings show that higher educational attainment and training participation will reduce the tendency for young fresh graduates to transition to the non-digital sector and choose to be unemployed, which indicates that it is consistent with work decision theory that the higher the investment in education and training, the higher the reservation wage will also be.